EFEKTIVITAS PENGAWASAN OMBUDSMAN DALAM MENANGANI KASUS MALADINISTRASI DI KOTA SEMARANG - Muhamad Akbar Arif Febriansyah; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
This study examines the effectiveness of the supervision carried out by the Ombudsman of the Republic of Indonesia in handling maladministration cases in the City of Semarang. The research is motivated by the persistence of maladministration practices in public services and the strategic role of the Ombudsman as an external supervisory institution in protecting citizens’ rights. This study employs a qualitative research method with a descriptive-analytical approach. Data were collected through in-depth interviews with the Ombudsman of the Republic of Indonesia Representative Office of Central Java, local government institutions, judicial institutions, and civil society organizations, complemented by document analysis and relevant regulations. The findings indicate that the Ombudsman’s supervision has contributed to improving public service responsiveness, administrative accountability, and the protection of citizens’ rights, particularly at the level of individual case resolution. The effectiveness of supervision is reflected in the follow-up of recommendations, procedural improvements, and administrative clarifications by reported institutions. However, the effectiveness remains conditional and has not yet reached an optimal level in terms of long-term structural impact. Limitations mainly stem from the non-binding nature of Ombudsman recommendations, variations in institutional compliance, and structural constraints within local government governance systems. This study concludes that the Ombudsman’s supervision can be categorized as moderately effective in handling maladministration cases in the City of Semarang, particularly in its corrective function, while its systemic and preventive impact requires stronger institutional integration and commitment from local government actors.